The Effect of Dragon Fruit Skin Juice in Drinking Water on Carcass And Carcass Part of Lohmann Brown Age of 52 Weeks - M., Sitepu; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This research aims to determine theeffect of dragon fruit peel juice in drinking water on carcass and carcass part of Lohmann Brown age of 52 weeks was conducted at Teaching Farm Campus Bukit Jimbaran, Badung, Bali during one month. The experiment used 45 heads of Lohmann Brown  age of 48 weeks. The experimental design used was a Complately Randomized Design (CRD) with three treatments and five replications, each replication consisted of 3 layers. The treatments were : driking water without dragon fruit peel juice (KBN 0 ), drinking water given 1% dragon fruit peel juice (KBN 1 ), and drinking water given dragon fruit peel juice 3% (KBN 2 ). The variabels observed were : slaughtering weight, carcass weight, carcass persentage, carcass part (chest, back, wings and thigh). The result showed that slaughtering weight, carcass weight, carcass persentage, carcass part (chest, back, wings and thight) in the KBN 0 , KBN 1 and KBN 2 treatments were not significantly different (P>0.05). Based on the result of the study it can be concluded that the given of dragon fruit peel juice in drinking water in the level of 1% and 3% does not effect the slaughtering weight, carcass percentage, carcass part (chest, back, wings and thight) of Lohmann Brown age of  52 weeks. Key words: juice skin dragon fruit, carcass, and each carcass, lohmann brown